-(2x-1)+3x=4x-5

Simple and best practice solution for -(2x-1)+3x=4x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(2x-1)+3x=4x-5 equation:


Simplifying
-1(2x + -1) + 3x = 4x + -5

Reorder the terms:
-1(-1 + 2x) + 3x = 4x + -5
(-1 * -1 + 2x * -1) + 3x = 4x + -5
(1 + -2x) + 3x = 4x + -5

Combine like terms: -2x + 3x = 1x
1 + 1x = 4x + -5

Reorder the terms:
1 + 1x = -5 + 4x

Solving
1 + 1x = -5 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
1 + 1x + -4x = -5 + 4x + -4x

Combine like terms: 1x + -4x = -3x
1 + -3x = -5 + 4x + -4x

Combine like terms: 4x + -4x = 0
1 + -3x = -5 + 0
1 + -3x = -5

Add '-1' to each side of the equation.
1 + -1 + -3x = -5 + -1

Combine like terms: 1 + -1 = 0
0 + -3x = -5 + -1
-3x = -5 + -1

Combine like terms: -5 + -1 = -6
-3x = -6

Divide each side by '-3'.
x = 2

Simplifying
x = 2

See similar equations:

| 6x+6y=o | | 3x+8+3x-2=180 | | 10s^2+5s= | | 3(t-6)+5t=4(2t+5)-13 | | 2(x-5)+3=-7 | | 3a^2-6a=3 | | (x+6)(x-4)=-16 | | 5v^2+32v+35=0 | | 2x(x-12)=40 | | 11x=180 | | x^3-5x-6=0 | | 5x^3-x^2-320x+64=0 | | 6x-45=538 | | a+6-6a=12+3a | | X=8-6y | | 7x+5y=-18 | | (4u+1)(8-u)=u | | t^2-11t+30=0 | | 3(-4x+1)=27 | | x=.85x+.45(80-x) | | t^2-4t+4=0 | | 3+3+3+3+3=10 | | -5x+40=160 | | 5t+2=9t-2 | | 4(5x-7)=-56 | | 12b=18 | | 2(x-9)=-5x-46 | | 6(3z-1)-4(z+3)=3(z+1) | | 7+4w=-5 | | 2ln(7x)=-4 | | 3x-5=2x-3 | | .54-.07y=.2y |

Equations solver categories